Evaluation of Antioxidant Levels in Blood Sera of Iraqi Patients with T2DM - Kadhim K. Ghudhib (Journal of Global Pharma Technology, 2018)
Back ground: oxidative stress is one of the problems that can encounter of diabetic patients. Reactive oxygen species formed as a result of oxidative stress. Antioxidants system serves to protection of cells from damage that may be occurred due the action of these species. In this work, we attempt to investigate the biochemical parameters including enzymatic and non- enzymatic antioxidants in patients with type 2 diabetic mellitus. Subjects and Methods: Blood samples were collected from 58 subjects include 29 males and 29 females, in age range of 40-72 years. They were classified into two groups, the first group represents patients group that include 30 patients. Second group consist of 28 healthy persons as a control group. BMI was calculated, fasting blood glucose, uric acid, urea and creatinine levels were measured by enzymatic methods. Glutathione peroxidase (GP x) and glutathione reductase (GR) levels were measured by enzyme linked immunosorbent assay (ELISA) method. Trace elements levels (zinc, magnesium and selenium) were estimated by flame atomic absorption spectrophotometer. Results: Results showed a significant increase in levels of FBG, UA, creatinine and significant decrease in levels of GP x, GR, Zn, MN, and Se in patents group related to the control group. There is no significant difference in level of urea between patients and control groups. Conclusion: Free radical generation increase in diabetic case, that lead to decrease in antioxidants levels of GPx1, GSR, Zinc, Selenium and Manganese. The levels of GPx1, GSR, Se, Zn, and Mn are the better indicators to evaluate the oxidative stress, and can be used as markers for early detection of diabetes.Keywords: T2DM, glutathione peroxidase, glutathione reductase, zinc, manganese, selenium.